STUDI DESKRIPTIF TEMPAT WUDHU ERGONOMI PADA LANJUT USIA (LANSIA) DI PANYABUNGAN, MANDAILING-NATAL - Yuli Aisyah Putri; Tri Niswati Utami (Jurnal Maternitas Kebidanan, 2021)
The level of comfort in performing ablution movements is very dependent on the shape of the ablution position, especially the height of the faucet and the movement position of the person standing or sitting for ablution, as well as the type of person who performs ablution. Purpose: to describe and describe the design of an ergonomic ablution place for the elderly in Panyabungan, Mandailing-Natal. Methods this study uses a qualitative method. The research approach used is a case study. Research informants were determined by purposive sampling consisting of key informants 3 elderly people, and 1 person from the mosque BKM. Supporting informants consist of 1 community leader, so the total informants are 5 people. Data analysis was collected by free-guided interviews using the Miles and Huberman technique. Processing using ATLAS.ti9 software. Result analysis of the data obtained that comfort affects the need for ablution facilities can be seen based on the value of the co-occurrence correlation coefficient (0.30). Based on ATLAS.ti9 analysis, 5 themes were obtained, namely: comfort, complaints, ablution time, frequency of use, and facility needs. Conclusion From the analysis it was found that the ablution place with a sitting position had the best value in this study, the need for facilities affected the comfort of ablution in the elderly, the floor in the ablution place was made flush with the road